Downregulation of miR-146b-3p Inhibits Proliferation and Migration and Modulates the Expression and Location of Sodium/Iodide Symporter in Dedifferentiated Thyroid Cancer by Potentially Targeting MUC20 - Hou, Shasha; Xie, Xiaorui; Zhao, Jing; Wu, Cailan; Li, Ning; Meng, Zhaowei; Cai, Chunquan; Tan, Jian (Frontiers in Oncology, 2021)
The dedifferentiated of differentiated thyroid cancer (DTC) is a difficult problem for radioactive iodine (131I) treatment, also known as radioiodine refractory differentiated thyroid cancer (RAIR-DTC), and the purpose of this study was to further explore the mechanism of the redifferentiation of dedifferentiated thyroid cancer. Ineffective and effective groups of 131I therapy were analyzed and compared both in our clinical and TCGA samples. Whole-exome sequencing, mutation analysis, transcriptome analysis and function experiments in vitro were conducted to reveal the potential biomarkers and mechanism of dedifferentiation and radioiodine therapy resistance. Concurrently, FLG, FRG1, MUC6, MUC20 and PRUNE2 were overlapped mutation genes between our clinical cases and TCGA case, only appeared in ineffective group. Moreover, the expression of miR-146b-3p target MUC20 were explored. The miR-146b-3p and MUC20 expression was significantly increased, and inhibition of the expression of miR-146b-3p significantly inhibited the proliferation and migration, promoted apoptosis and regulated the expressions and location of thyroid differentiation-related genes, sodium/iodide symporter (NIS) in dedifferentiated thyroid cancer cells (WRO). This study demonstrates that miR-146b-3p potentially targeting MUC20 participated in the formation of DTC dedifferentiation, which resulted in resistance to 131I and loss of iodine uptake ability of DTC cancer foci, and become refractory differentiated thyroid cancer, and miR-146b-3p could be a potentially therapeutic target for reapplication of 131I therapy in dedifferentiated thyroid cancer patients.